2010
DOI: 10.2478/v10042-010-0058-3
|View full text |Cite
|
Sign up to set email alerts
|

Fas/FasL expression in colorectal cancer. An immunohistochemical study.

Abstract: Materials and methodsTissue samples. The study group consisted of 50 patients with colorectal carcinoma, operated on in the Surgical Department of the J. Sniadecki Hospital in Bialystok. Colorectal carcinoma specimens FOLIA HISTOCHEMICA ET CYTOBIOLOGICA Vol. 48, No. 3, 2010 pp. 425-429 Fas/FasL expression in colorectal cancer. An immunohistochemical study Anna Pryczynicz, Katarzyna Guziñska-Ustymowicz and Andrzej Kemona Department of General Pathomorphology, Medical University of Bia³ystok, Bia³ystok, Pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…The main components of the lymphoid cells are CD4+ T helper cells, CD8+ cytotoxic lymphocytes, and natural killer cells (Torisu et al, 2000). After Clark's classic article demonstrating the positive relationships between lymphoid cells and prognosis, this fact has been widely accepted and supported for several cancer types (Clark et al, 1989;Okada et al, 2000;Reichert et al, 2002;Kase et al, 2003;Guo et al, 2008;Bozdogan et al, 2010;Pryczynicz et al, 2010), including head and neck cancer (Fang et al, 2013;Mendes et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The main components of the lymphoid cells are CD4+ T helper cells, CD8+ cytotoxic lymphocytes, and natural killer cells (Torisu et al, 2000). After Clark's classic article demonstrating the positive relationships between lymphoid cells and prognosis, this fact has been widely accepted and supported for several cancer types (Clark et al, 1989;Okada et al, 2000;Reichert et al, 2002;Kase et al, 2003;Guo et al, 2008;Bozdogan et al, 2010;Pryczynicz et al, 2010), including head and neck cancer (Fang et al, 2013;Mendes et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Gastman et al (1999) showed that FASL expression in head and neck squamous cell carcinoma promotes tumor inflammatory infiltrate cell apoptosis. In the same line, Reichert et al (2002) analyzed the correlation between FASL expression in OSCC and apoptosis index in the inflammatory infiltrate, suggesting that the tumor can alter immune cell survival via the FAS/FASL pathway, since most circulating T-cells are FAS+ and are therefore susceptible to apoptosis through interaction of FASL with its receptor (Okada et al, 2000;Hoffmann et al, 2002;Pryczynicz et al, 2010). Moreover, in colorectal cancer other authors have shown that lymphoid cell apoptosis is higher when FASL expression is strong (Bennett et al, 1998;Okada et al, 2000;Pryczynicz et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In malignant tumor diseases, the expression of Fas might be reduced on the surface of tumor cells in order to escape the removal functions of immune cells, enabling tumor cells to seize proliferation opportunities resulting in disease. Fas expression increases in autoimmune diseases, such as systemic lupus erythematosus, multiple sclerosis, and Grave's disease, which causes immune cells to identify and kill their own organizations (Ehrenschwender and Wajant, 2009;Pryczynicz et al, 2010;Otsuki et al, 2011). The results of the present study showed that FasL expression on the CD8 + T cell surface was significantly higher in SAA patients compared to the normal population.…”
Section: Discussionmentioning
confidence: 99%